2015
DOI: 10.37236/3933
|View full text |Cite
|
Sign up to set email alerts
|

The Distinguishing Index of Infinite Graphs

Abstract: The  distinguishing index $D^\prime(G)$ of a graph $G$ is the least cardinal $d$ such that $G$ has an edge colouring with $d$ colours that is only preserved by the trivial automorphism. This is similar to the notion of the distinguishing number $D(G)$ of a graph $G$, which is defined with respect to vertex colourings.We derive several bounds for infinite graphs, in particular, we prove the general bound $D^\prime(G)\leq\Delta(G)$ for an arbitrary infinite graph. Nonetheless,  the distinguishing index is at mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…We need one more definition and a theorem proved by Broere and Pilśniak in . Let x be a vertex in G.…”
Section: Bound For Graphs With Normalδ(g)goodbreakinfix=3mentioning
confidence: 99%
“…We need one more definition and a theorem proved by Broere and Pilśniak in . Let x be a vertex in G.…”
Section: Bound For Graphs With Normalδ(g)goodbreakinfix=3mentioning
confidence: 99%
“…They also introduced the distinguishing chromatic index χ D (G) as the minimum number of colours needed to properly colour the edges of G such that this edge colouring is only preserved by the trivial automorphism. Furthermore, they showed that χ D (G) ∆(G) + 1 except for C 4 , K 4 , C 6 and K 3,3 . Therefore, except for these four small graphs, we have χ D (G) χ (G) + 1, a result which is also true for infinite graphs, as we show in Section 4.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Broere and Pilśniak [3] considered D (G) for infinite graphs. They proved that for every connected infinite graph we have D (G) ∆, where ∆ is a cardinal number such that degree of any vertex is at most ∆.…”
Section: Introductionmentioning
confidence: 99%
“…While Tucker's conjecture is still wide open, there are many partial results towards it, see [3,6,7,10,11,14,16]. Broere and Pilśniak [2] noticed that most of these partial results can be generalised to edge colourings. Consequently, they conjecured that an analogous statement to Conjecture 1 should hold in the realm of edge colourings.…”
Section: Introductionmentioning
confidence: 99%
“…Conjecture 2 (Infinite edge motion conjecture [2]). Let G be a countable, connected graph and assume that every automorphism of G moves infinitely many edges.…”
Section: Introductionmentioning
confidence: 99%